Evaluasi Pengelolaan Keuangan Desa Sesuai Dengan Peraturan Menteri Dalam Negeri No. 20 Tahun 2018 Pada Desa Libunio Kecamatan Soa Kabupaten Ngada - Yovita Eno Meo; Sodik Sodik; Dwi Anggarani (CV. ITTC INDONESIA, 2025)
This descriptive qualitative research evaluates the conformity of financial management in Libunio Village with the Ministry of Home Affairs Regulation (Permendagri) No. 20 of 2018. The results show that a high level of administrative compliance has been achieved (the principles of Orderliness and Budget Discipline are fulfilled through the use of SISKEUDES). However, the analysis indicates that transparency needs to be enhanced by providing more open access to village financial information for the public, for example, through the establishment of a village website and community radio as stipulated in the regulation. It is concluded that the Village Government needs to strengthen its means of publication and the use of information media to fully realize the effectiveness of the transparency principle in accordance with the provisions of Permendagri.